The impact of physical activity and diet therapy on improving metabolic syndrome - Tambovtseva, R.V.; Nikulina, I.A.; Pletneva, E.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to assess the impact of caloric intake and physical activity on insulin resistance in elderly women. Methods and structure of the study. Content analysis of articles by domestic and foreign authors. MAXQDAAnaleticsPro software was used to analyse the data. Results and conclusions. Insulin resistance is associated with impaired cell metabolism in response to insulin when its concentration in the human body is sufficient. This pathology is more common in men over the age of 30, while in women, insulin resistance increases several times after the age of 45-50. Today, there are many aetiological factors contributing to the development of this metabolic disorder: genetic predisposition, high insulin concentration in the treatment of type I diabetes mellitus, a sedentary lifestyle, arterial hypertension, prolonged consumption of low-calorie foods and, conversely, excessive consumption of foods containing large amounts of carbohydrates and fats, alcoholism, hormonal imbalances, taking certain hormonal medications, as well as stress factors.